2002
DOI: 10.1152/ajpgi.00149.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of TNF-α in gut mucosal changes after severe burn

Abstract: Gut epithelial cell death by apoptosis is increased in the gut epithelium after severe burn associated with mucosal atrophy. We hypothesized that tumor necrosis factor (TNF)-α-TNF receptor (TNFR) interaction activates apoptosis in small bowel mucosal cells after severe burn. C57BL6 mice received a 30% total body surface area scald burn and were treated with neutralizing anti-TNF-α. The proximal small bowel was assessed for mucosal atrophy. Proliferation and apoptosis of mucosal cells were assessed by prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 21 publications
0
34
1
Order By: Relevance
“…Local intestinal TNF-␣ production may not change, despite significant increases in serum levels (58). Along these lines, administration of a neutralizing antibody to TNF-␣ was shown to prevent the increased enterocyte apoptosis following burn injury, despite the fact that no changes were identified in intestinal TNF-␣ mRNA expression (48). Although serum levels were not measured after SBR in the present study, no significant alterations in circulating levels of TNF-␣ were revealed in a previous report of rats undergoing a 70% SBR (31).…”
Section: Discussioncontrasting
confidence: 48%
“…Local intestinal TNF-␣ production may not change, despite significant increases in serum levels (58). Along these lines, administration of a neutralizing antibody to TNF-␣ was shown to prevent the increased enterocyte apoptosis following burn injury, despite the fact that no changes were identified in intestinal TNF-␣ mRNA expression (48). Although serum levels were not measured after SBR in the present study, no significant alterations in circulating levels of TNF-␣ were revealed in a previous report of rats undergoing a 70% SBR (31).…”
Section: Discussioncontrasting
confidence: 48%
“…The significant decrease in small bowel weight following MTX treatment implies the presence of mucosal atrophy. 21 In accordance with this, the morphological appearance of the intestinal mucosa was characterized by epithelial desquamation and vacuolization, with an extensive loss of goblet cells. The inflamed intestines demonstrate the presence of oxidant injury, with elevated lipid peroxidation and depleted glutathione levels, which were accompanied by neutrophil accumulation, indicating a possible source of this oxidant injury.…”
Section: Discussionmentioning
confidence: 53%
“…Image capture and density analysis of bands was done with the SynGene gel documentation system (SynGene-Synoptics, Cambridge, UK), and the intensity of bands was expressed as the ratio of HSP70 to ␤-actin (36). Western blot analysis.…”
mentioning
confidence: 99%